Myelin and Modeling: Bootstrapping Cortical Microcircuits - Turner, Robert (Frontiers in Neural Circuits, 2019)
Histological studies of myelin-stained sectioned cadaver brain and in-vivo myelin-weighted magnetic resonance imaging show that the cerebral cortex is organized into cortical areas with generally well-defined boundaries, which have consistent internal patterns of myelination. The process of myelination is largely driven by neural experience, in which the axonal passage of action potentials stimulates neighbouring oligodendrocytes to perform their task. This bootstrapping process, such that the traffic of action potentials facilitates increased traffic, suggests the hypothesis that the specific pattern of myelination (myeloarchitecture) in each cortical area reveals the principal cortical microcircuits required for the function of that area. If this idea is correct, the observable sequential maturation of specific brain areas can provide evidence for models of the stages of cognitive development.